Writing from the margins: multiple subalternity of Rokeya Sakhawat Hossain - Hasan, Md. Mahmudul (Department of English Language and Literature, KIRKHS, International Islamic University Malaysia, 2018)
Rokeya Sakhawat Hossain came from and wrote for a colonised, marginalised society. Hence, the question of the silenced subaltern voice and agency, and of subordinate experiences of non-Western writers is pertinent to the discussion of her work. She is a subaltern not only because of gender and colonial differences, but also because of her ethnic, religious and other identities. She is subordinated as a writer of a colonised society and marginalised as a Muslim feminist scholar. Various factors that contributed to her subalternity were enmeshed together and became grounds for her marginal status among regional and global feminist writers. Based on this theoretical background, this article will discuss the term ‘subaltern’ and examine factors that contributed to Rokeya’s subalternity.